2017
DOI: 10.11646/zootaxa.4227.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear markers support the mitochondrial phylogeny of Vipera ursinii–renardi complex (Squamata: Viperidae) and species status for the Greek meadow viper

Abstract: Meadow vipers (Vipera ursinii-renardi complex) are small-bodied snakes that live in either lowland grasslands or montane subalpine-alpine meadows spanning a distribution from France to western China. This complex has previously been the focus of several taxonomic studies which were based mainly on morphological, allozyme or immunological characters and did not clearly resolve the relationships between the various taxa. Recent mitochondrial DNA analyses found unexpected relationships within the complex which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 496 publications
(36 citation statements)
references
References 31 publications
3
33
0
Order By: Relevance
“…The Greek Meadow Viper, Vipera graeca (Nilson & Andrén, ), is a poorly known cold‐adapted snake living in alpine meadows between 1,600 and 2,200 m above sea level in the Pindos mountain range in Albania and Greece (Mizsei et al, ). Originally described as a subspecies, molecular studies confirmed the lineage as basal to the entire complex (Ferchaud et al, ; Nilson & Andrén, ) and was subsequently elevated to species level (Mizsei, Jablonski, Roussos, et al, ). Vipera graeca is listed as endangered in the IUCN Red List due to its small and severely fragmented distribution, ongoing habitat degradation (mostly by overgrazing), mortality from intentional killing by shepherds and vulnerability to climate change (Mizsei, Szabolcs, Dimaki, Roussos, & Ioannidis, ; Mizsei, Szabolcs, et al, ).…”
Section: Methodsmentioning
confidence: 95%
“…The Greek Meadow Viper, Vipera graeca (Nilson & Andrén, ), is a poorly known cold‐adapted snake living in alpine meadows between 1,600 and 2,200 m above sea level in the Pindos mountain range in Albania and Greece (Mizsei et al, ). Originally described as a subspecies, molecular studies confirmed the lineage as basal to the entire complex (Ferchaud et al, ; Nilson & Andrén, ) and was subsequently elevated to species level (Mizsei, Jablonski, Roussos, et al, ). Vipera graeca is listed as endangered in the IUCN Red List due to its small and severely fragmented distribution, ongoing habitat degradation (mostly by overgrazing), mortality from intentional killing by shepherds and vulnerability to climate change (Mizsei, Szabolcs, Dimaki, Roussos, & Ioannidis, ; Mizsei, Szabolcs, et al, ).…”
Section: Methodsmentioning
confidence: 95%
“…Further mitochondrial and nuclear DNA evidences also support the species status of these lineages (Zinenko et al 2015;Mizsei et al, 2017). A recent taxonomic change has also influenced the current known distribution of this group, as the Greek meadow viper Vipera graeca, a former subspecies of V. ursinii, was elevated to the species level (Mizsei et al, 2017). Additionally, most of the distribution within the former Soviet Union is poorly understood because of the lack of accessible observation records.…”
mentioning
confidence: 88%
“…The latter was not accepted previously as a full species by the Societas Europaea Herpetologica (SEH) (footnote 9 on table 3 in Sillero et al, 2014a), despite that species delimitation between V. ursinii and V. renard i had been proved or discerned (Nilson Andrén, 2001;Ferchaud et al, 2012;GvoŽdík et al, 2012). Further mitochondrial and nuclear DNA evidences also support the species status of these lineages (Zinenko et al 2015;Mizsei et al, 2017). A recent taxonomic change has also influenced the current known distribution of this group, as the Greek meadow viper Vipera graeca, a former subspecies of V. ursinii, was elevated to the species level (Mizsei et al, 2017).…”
mentioning
confidence: 88%
“…This is not a rule, especially in mountain "sky-islands" species of the region with scattered distribution in current interglacial refugia (see Podnar et al 2014;Mizsei et al 2017).…”
Section: Acknowledgementsmentioning
confidence: 99%